Labeling food safety attributes: To inform or not to inform? - Kofi Britwum; Amalia Yiannaka (Agricultural and Food Economics, 2019)
We examine the impact of food labels that make unsupported claims of food safety and labels that provide information to support such claims on consumer choices and examine consumers' willingness to pay for beef products with these different food safety labeling cues. Empirical results from a survey of grocery shoppers in a Midwestern city in the USA show that more than two thirds of respondents who received a label with unsubstantiated food safety claims chose this option and were willing to pay the highest price premium for it, compared to the less preferred labeling options that provided information to support food safety claims.
Keywords: D12; Q13; Q18; 330; Food labels; Ground beef; Survey; Vaccines against E. coli; Willingness to pay